CONSIDERAÇÕES SOBRE A MELHORIA DO PROCESSO ENSINO-APRENDIZAGEM EM MATEMÁTICA BASEADAS NA ORIENTAÇÃO AO PROCESSO E NA INVESTIGAÇÃO MATEMÁTICA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The main objective of this work is to present and research a teaching-learning methodology that leads to the classroom a more favorable environment for the assimilation of mathematical concepts, providing an education with greater potential for encouragement of learner autonomy. Initially we present a historic review ofmathematics education, their prospects for education and his trajectory in Brazil. We approach as central and fundamental point of the constructivist methodology, this is characterized by enhancing and valorizing the knowledge constructions made by the learners themselves, and in this sense, we are engaged in defending it as a feasible alternative to the math education. In order to provide a constructivist environment, we described some investigation scenarios where the teacher goes to address mathematical content in order to stimulate students to think, analyze and investigate.This process of encouragement for the student’s autonomy in building his knowledge was corroborated through a proposal of investigative activity applied in the teaching of proportionality and rule of three, which proved a viable and effective strategy for a more meaningful learning of mathematical concepts.
Keywords: autonomia; construtivismo; educação matemática; ensino aprendizagem; investigação matemática; autonomy; constructivism; mathematics education; teaching- learning process; mathematical investigation; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA